Comparison of the Effectiveness of Lidocaine in Permanent Maxillary Teeth Removal Performed with Single Buccal Infiltration Versus Routine Buccal and Palatal Injection - Kumaresan, Ramesh (J Maxillofac Oral Surg, 2014)
PURPOSE: For many dental patients, palatal injection proves to be a very traumatic experience. Diverse methods have been suggested to reduce the discomfort of palatal injection. Nevertheless, the reliability of these methods is not obviously evident and they are not found to be universally effective. The desirable method to evade pain during palatal injection is just not to have one. Hence, the present study aims at investigating if lidocaine hydrochloride could provide palatal anesthesia in maxilla when only a buccal infiltration anesthesia is done for teeth extraction. PATIENTS AND METHODS: One hundred and fifty patients requiring extraction of maxillary teeth were included in the study. Patients were randomly allotted to two groups, study and control. Patients in study group received a single buccal infiltration of 1.5 mL of lidocaine with epinephrine for extraction of maxillary teeth. Patients in control group received 1.5 mL of buccal and 0.3 mL of palatal infiltration of lidocaine with epinephrine for the extraction. After achieving adequate palatal anesthesia the tooth was extracted with consistent technique. Pain level experienced by the patients during injection procedure and during tooth extraction was rated in an 11-point pain rating scale. Time taken to achieve palatal anesthesia following a single buccal infiltration of anesthetic solution was evaluated by regular pin-prick evaluation of palatal tissues. RESULTS: The overall success rate of palatal anesthesia achieved with a single buccal infiltration is 81.3 %. The success rate reduced as we proceed from anterior to posterior maxilla. Time taken to achieve successful palatal anesthesia by single buccal infiltration is 7–9 min. CONCLUSION: The extraction of permanent maxillary anterior teeth and premolars is possible by depositing local anesthesia to the buccal vestibule of the tooth without palatal supplementation. However, the extraction of permanent maxillary posterior teeth with similar technique would result in fewer success rates suggesting its avoidance.